2020
DOI: 10.1109/access.2019.2963399
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Swing Up Control and Optimal State Feedback Stabilization for Self-Erecting Inverted Pendulum

Abstract: This paper presents the realisation of self-erecting inverted pendulum controls via two switched control approaches, a rule based fuzzy control for swing up inverted pendulum rod to pose upright position from downright position and an optimal state feedback control for stabilization as pendulum on upright position close to its equilibrium vertical line. The aim of this study is to solve two important problems on self-erecting inverted pendulum; swing up and stability in its upright balance position. Simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…The authors reported a settling time of 5 seconds. In [16], the authors utilized a hybrid controller approach using fuzzy logic control for swing up controller, switching to state feedback control for stabilization, and using LQR (guaranteed cost control) for uncertainty handling. The authors reported a settling time of 7.7 seconds.…”
Section: Comparison Of Proposed Controller With State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported a settling time of 5 seconds. In [16], the authors utilized a hybrid controller approach using fuzzy logic control for swing up controller, switching to state feedback control for stabilization, and using LQR (guaranteed cost control) for uncertainty handling. The authors reported a settling time of 7.7 seconds.…”
Section: Comparison Of Proposed Controller With State-of-the-artmentioning
confidence: 99%
“…The controller gain matrix was further optimized by adding Kalman filter. In [16], authors developed a fuzzy controller based on a guaranteed cost control objective function for swing up control of the inverted pendulum system. The controller is built around the linearized model of the inverted pendulum system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this research, the value of m is fixed at unity. The selected coefficients of Q and R matrices are shown in (9).…”
Section: Primary State-feedback Controllermentioning
confidence: 99%
“…However, the offline selection of fractional orders is an ill-posed problem. The fuzzy controllers, despite their flexibility, require elaborate qualitative logical rules and offline tuning of a multitude of parameters to deliver robust control effort [9]. The sliding mode controllers, despite their robustness, unavoidably inject chattering in the system's response [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…A robustness test has also been conducted to ensure that the determination of controller type is proper. An impulse disturbance can be applied to test the robustness of a controller [19]. The test considers that balancing bicopter is initially in a hovering position.…”
Section: B Ziegler-nichols Based Pid Controllermentioning
confidence: 99%